Meta-analysis of QTL for Fusarium head blight resistance in Chinese wheat landraces using genotyping by sequencing - Cai, Jin (Kansas State University, 2016)
Fusarium head blight (FHB) is a devastating fungal disease in wheat, reducing not only grain yield but also quality. The pathogen produces the mycotoxin deoxynivalenol (DON) that induces severe toxicological problems in human and animals. Using host resistance has been the most efficient way to control the disease. To identify quantitative trait loci (QTLs) for FHB resistance in Chinese landrace Haiyanzhong (HYZ), a recombinant inbred lines (RILs) population derived from a cross between HYZ and Wheaton was developed. The RILs were evaluated for percentage of symptomatic spikelets (PSS) in three greenhouse experiments, and genotyped using simple sequence repeats (SSRs) and single nucleotide polymorphism (SNPs) developed from genotyping-by-sequencing (GBS). Eight QTLs were identified for type II (PSS) resistance on chromosomes 5A, 6B, 7D, 2B (2), 3B, 4B, and 4D, with 5A as the major QTL. Ten SNPs closely linked to 5A, 6B, and 2B QTLs were successfully converted to Kompetitave allelic specific PCR (KASP) assays. To identify common QTLs across different populations, we constructed high-density GBS-SNP maps in an additional four RIL populations derived from the Chinese landraces, Wangshuibai (WSB), Baishanyuehuang (BSYH), Huangfangzhu (HFZ), and Huangchandou (HCD) and conducted meta-analysis of the QTLs for FHB resistance using a consensus map developed from the five populations. We identified six MQTLs on chromosomes 3BS (2), 3A, 3D, 2D, and 4D and 23 tightly linked GBS-SNPs to the MQTLs. These GBS-SNPs were successfully converted to KASPs. The KASPs linked to MQTLs can be used for pyramiding these QTL in breeding programs. To quickly reduce FHB damage in U.S. hard winter wheat (HWW), we transferred Fhb1, a major QTL with stable effects on FHB resistance, from Ning7840 into three adapted HWW cultivars Overland, Jagger, and Overley, by marker-assisted backcross (MAB), and assessed the effect of Fhb1 on FHB resistance in these different backgrounds. The results showed that Fhb1 can significantly lower FHB severity, Fusarium-damaged kernel (FDK), and DON accumulation in the all the three HWW backgrounds. Some of the selected lines showed high levels of FHB resistance, but agronomically similar traits as recurrent parents, can be used as resistant parents to improve HWW FHB resistance.
Keywords: SNP; KASP; Meta-analysisGenotyping-by-sequencing; Triticum aestivum L.